2011
DOI: 10.1016/j.vetmic.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and extra-intestinal pathogenicity of a bovine reassortant rotavirus in calves and piglets

Abstract: Despite the impact of bovine group A rotaviruses (GARVs) as economically important and zoonotic pathogens, there is a scarcity of data on cross-species pathogenicity and extra-intestinal spread of bovine reassortant GARVs. During the course of characterizing the genotypes of all 11 genomic segments of bovine GARVs isolated from diarrheic calves in South Korea, a unique G6P[7] reassortant GARV strain (KJ9-1) was isolated. The strain harbors five bovine-like gene segments (VP7: G6; VP6: I2; VP1: R2; VP3: M2; NSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(76 citation statements)
references
References 56 publications
3
72
0
1
Order By: Relevance
“…The presence of RVA in MLNs has so far been reported in experimental animal models (Brown & Offit, 1998;Crawford et al, 2006;Dharakul et al, 1988;Fenaux et al, 2006;Kim et al, 2011;Mossel & Ramig, 2003; Park et al, Genetic analyses showed that all strains for which the genome was detected in MLNs from autopsied calves and healthy adult cattle were classified as G and/or P (possible) genotypes generally prevalent in bovines (Tables 2 and 3). Also, in most of the cattle that had RVA genomes in both MLNs and intestinal contents, the strains in intestinal contents were genetically identical to those in MLNs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The presence of RVA in MLNs has so far been reported in experimental animal models (Brown & Offit, 1998;Crawford et al, 2006;Dharakul et al, 1988;Fenaux et al, 2006;Kim et al, 2011;Mossel & Ramig, 2003; Park et al, Genetic analyses showed that all strains for which the genome was detected in MLNs from autopsied calves and healthy adult cattle were classified as G and/or P (possible) genotypes generally prevalent in bovines (Tables 2 and 3). Also, in most of the cattle that had RVA genomes in both MLNs and intestinal contents, the strains in intestinal contents were genetically identical to those in MLNs.…”
Section: Discussionmentioning
confidence: 94%
“…Also, previous studies on the dynamics of RVA in extra-intestinal organs in calves under experimental conditions showed that MLNs had the highest viral RNA copy number amongst extra-intestinal organs (Kim et al, 2011;Park et al, 2013Park et al, , 2014. It was also reported that viral RNA copy numbers in MLNs were comparable to or sometimes higher than those in faeces through the duration of experimental infection for 14 days.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…At 7 days post-infection, four mice from each group were killed and the small intestine of each group were collected for histopathological examinations. The changes in small intestinal were scored as described by Kim et al [41]. Based on the ratios of villi/crypt (V/C) which estimated as follows: 0 = normal, 1 = mild, 2 = moderate, 3 = marked and 4 = severe.…”
Section: Antiviral Activity Of Methanol Extract Of D Viscosa On Cvb3mentioning
confidence: 99%
“…In children who died during RVA infection, RVA antigens and viral RNA were detected in the extraintestinal organs and tissues including the central nervous system, liver, lung, spleen, heart, kidney, testis, and bladder (Blutt and Conner, 2007;Lynch et al, 2001;Pager et al, 2000;Ramig, 2004;Riepenhoff-Talty et al, 1996;Zheng et al, 1991). It has been clearly demonstrated that RVAs cause not only gastrointestinal but also systemic infections in experimental animal models (Ciarlet et al, 2002;Crawford et al, 2006;Fenaux et al, 2006;Kim et al, 2011Kim et al, , 2012bPetersen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%